EFFECT OF HILLING ABOVE MULCH AND TYPES OF RETARDANT ON GROWTH AND PRODUCTION OF POTATO (Solanum tuberosum L.) MEDIANS CULTIVAR IN MEDIUM ALTITUDE - Nadia Uliati; Jajang Sauman Hamdani; Rahmat Budiarto (Gunung Djati Conference Series, 2026)
Potato (Solanum tuberosum L.) cultivation in medium-altitude regions faces the primary challenge of high temperatures that inhibit stolon initiation and tuber formation. This study aimed to determine the effect of hilling above mulch and the application of growth retardants prohexadione-Ca and paclobutrazol on the growth and production of Medians potato cultivar at medium altitude. The experiment was conducted from October 2025 to February 2026 at PT. Central Horti Agro Makro, Cisurupan District, Garut, West Java (±800 m asl) using a Split Plot Design. The main plot consisted of hilling treatments (b₁: no mulch, no hilling; b₂: hilling without mulch; b₃: mulch without hilling; b₄: mulch with hilling) and the subplot consisted of retardant types (r₀: no retardant; r₁: prohexadione-Ca 100 ppm; r₂: paclobutrazol 100 ppm), replicated three times. Results showed that paclobutrazol 100 ppm significantly suppressed plant height at 60 DAP (33.20 cm) compared to prohexadione-Ca (37.80 cm) and the control (42.21 cm). No significant differences were observed among treatments for leaf area index (1.23 – 2.00). The b₄ treatment produced the highest total stolon count (15.33) and tuber number (12.89 knols plant-1). Prohexadione-Ca 100 ppm yielded the highest tuber number per plant (11.83 knols), while paclobutrazol 100 ppm produced the highest tuber weight per plant (178.11 g). The b₄ treatment also yielded the highest tuber weight (260.11 g plant-1), demonstrating a synergistic effect between mulching, hilling, and retardant application in improving potato production at medium altitude.